Ray-Traced Reflections in Real-Time Using Heuristic Based Hybrid Rendering - Andrade, Paulo; Sabino, Thales; Clua, Esteban; Pagliosa, Paulo (2014 Brazilian Symposium on Computer Games and Digital Entertainment, 2014)
Game engines typically use cube maps or screen space local reflections for simulating reflections effects at the real-time renderer pipeline. While these techniques work in many situations, they cannot deal well with reflections of reflections, reflections from covered spaces, reflections from elements outside the screen space or reflections from elements that change its shape or position in real-time. In this paper, we present a method capable of creating true real-time ray-traced reflections by using a heuristic based method and a hybrid renderer. Our solution maintain real-time frame rates by selecting, for each frame, the best reflexive surfaces to ray trace, based on the user's point of view.